MicroRNA Deficiency in VIP+ Interneurons Leads to Cortical Circuit Dysfunction. (4th November 2019) - Qiu, Fang; Mao, Xingfeng; Liu, Penglai; Wu, Jinyun; Zhang, Yuan; Sun, Daijing; Zhu, Yueyan; Gong, Ling; Shao, Mengmeng; Fan, Keyang; Chen, Junjie; Lu, Jiangteng; et al.
Abstract: Genetically distinct GABAergic interneuron subtypes play diverse roles in cortical circuits. Previous studies revealed that microRNAs (miRNAs) are differentially expressed in cortical interneuron subtypes, and are essential for the normal migration, maturation, and survival of medial ganglionic eminence-derived interneuron subtypes. How miRNAs function in vasoactive intestinal peptide expressing (VIP + ) interneurons derived from the caudal ganglionic eminence remains elusive. Here, we conditionally removed Dicer in postmitotic VIP + interneurons to block miRNA biogenesis. We found that the intrinsic and synaptic properties of VIP + interneurons and pyramidal neurons were concordantly affected prior to a progressive loss of VIP + interneurons. In vivo recording further revealed elevated cortical local field potential power. Mutant mice had a shorter life span but exhibited better spatial working memory and motor coordination. Our results demonstrate that miRNAs are indispensable for the function and survival of VIP + interneurons, and highlight a key role of VIP + interneurons in cortical circuits.